Making Work Pay': in a rationed labour market - Olivier Bargain; Marco Caliendo; Peter Haan; Kristian Orsini (Institute for the Study of Labor (IZA), 2006)
We assess the labour supply effects of two 'making work pay' reforms in Germany. We provide evidence in favour of policies that distinguish between low effort and low productivity by targeting individuals with low wages rather than individuals with low earnings. In assessing the policies we account for demand-side constraints by using a double-hurdle model. We identify and decompose the potential bias of labour supply elasticities derived in standard unconstrained models. Although this bias is not significant when assessing policies which mainly target voluntarily unemployed workers (typically secondary earners), it is substantial for policies which affect groups with high shares of involuntary unemployment.
Keywords: C25; C52; H31; J22; 330; tax-benefit systems; microsimulation; household labour supply; multinomial logit; involuntary unemployment; double-hurdle; Arbeitsangebot; Privater Haushalt; Arbeitsmarktpolitik; Niedriglohn; Niedrigeinkommen; Beschäftigungseffekt; Schätzung; Deutschland